Studies for air traffic management R&D in the ASEAN-region context. (September 2017) - Zhong, Z.W.; Varun, Dhir; Lin, Y.J.
Abstract: We investigated flight delays and found that thunderstorms largely affected the flight delay duration. By performing Monte Carlo simulations, we also examined several scenarios to estimate the airport runway capacity. The results found might allow identifying crucial factors, meeting the rising air transport demand for more years ahead. In addition, a functioning modelling and simulation capability was established by the Air Traffic Management Research Institute to carry out analyses of traffic flows and airspace structures throughout the ASEAN region and to provide solutions for capacity and efficiency enhancements. Highlights: We found that thunderstorms largely affected the flight delay duration. By performing Monte Carlo simulations, we examined several scenarios and the runway capacity. The results allow identifying crucial factors, meeting the rising demand for years ahead. A functioning modelling and simulation capability was established for analyses of airspace structures.